SYSTEMATIC LITERATURE REVIEW: STUDENTS' SELF EFFICACY BASED ON MATHEMATICAL REFLECTIVE THINKING ABILITY - Izzatunnisa, Rega; Novaliyosi, Novaliyosi; Fatah, Abdul (Journal of Authentic Research on Mathematics Education (JARME), 2025)
This study is a literature review that aims to describe the differences  in self-efficacy based on mathematical reflective thinking ability and identify factors that affect self-efficacy in improving mathematical reflective thinking ability, The research method used is systematic literature review by involving a detailed analysis of various selected articles using  the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. The literature search process through the Publish or Perish application  uses academic databases such as SINTA, Google Scholar, Garuda. The results of the search for related articles out of 50 articles were selected 20 articles based on special criteria in the literature review in this study. The results of the literature review showed that  high self-efficacy encouraged individuals to actively face and solve complex mathematical challenges. They were more confident in making analogies from two similarities, which increased their desire to develop reflective thinking strategies. In contrast, students with  low self-efficacy tend to accept answers without considering other options and are more passive in the reflection process. Factors such as a supportive learning environment, the presence of inspiring role models, positive feedback, intrinsic motivation, and the ability to engage in continuous self-reflection all play a role in strengthening self-efficacy in the context of mathematical reflective thinking skills.